2018
DOI: 10.1002/jia2.25151
|View full text |Cite
|
Sign up to set email alerts
|

A prospective “test‐and‐treat” demonstration project among people who inject drugs in Vietnam

Abstract: IntroductionModelling suggests that early diagnosis and immediate antiretroviral therapy (ART) among key populations would have a substantial impact in reducing HIV transmission and mortality in Vietnam. An implementation research project of “test‐and‐treat” among people who inject drugs (PWID) was developed to inform effective roll‐out of such interventions.Methods“Test‐and‐treat” was offered to PWID in two high burden provinces, Thai Nguyen and Thanh Hoa. The interventions comprised the offer of biannual HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
(18 reference statements)
2
4
0
Order By: Relevance
“…As a probable consequence of the test-and-treat strategy, CD4 measurements were no longer measured systematically prior to ART initiation, indeed only 28% of the patients had a CD4 measurement. In this group, the median (IQR) CD4 level was 287 (83-449) cells/mm 3 , which is higher than in previous reports in Vietnam [24,29] and in line with the global increase of CD4 level at ART initiation observed in resource-limited settings [30].…”
Section: Plos Onesupporting
confidence: 77%
See 2 more Smart Citations
“…As a probable consequence of the test-and-treat strategy, CD4 measurements were no longer measured systematically prior to ART initiation, indeed only 28% of the patients had a CD4 measurement. In this group, the median (IQR) CD4 level was 287 (83-449) cells/mm 3 , which is higher than in previous reports in Vietnam [24,29] and in line with the global increase of CD4 level at ART initiation observed in resource-limited settings [30].…”
Section: Plos Onesupporting
confidence: 77%
“…In terms of virological results, the proportion of patients with a viral load <1000 copies/mL at 6 months was 84.2%. This is lower than other evaluations which took place at later time points [23,24,31], but similar to the proportion observed in a test-and-treat evaluation study in PWID performed in Vietnam [29]. At later time points, the higher rate of virological success could be explained by a survival bias effect as those who were not fully adherent are no longer in active care.…”
Section: Plos Onesupporting
confidence: 67%
See 1 more Smart Citation
“…Recent studies in Vietnam have also suggested that enacted and anticipated stigma was common among PWID, and that stigmatization by health care providers was an important barrier for PWID to access services. [48][49][50] For example, health care providers often described patients using terms like lazy, unreliable and viewed PWID as unable to prioritize HIV treatment and care. 49 While our participants rarely reported explicit stigmatization from health care providers, many reported providers being silent, cold, or not allowing questions from patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is supported by a few studies that showed that the mortality rate in HIV-positive MMT clients was low with early ART initiation, and the combined treatment increased the retention rate in the MMT program. [ 2 4 , 17 18 ]…”
Section: Discussionmentioning
confidence: 99%